SOCIAL-COMMERCIAL INTERCONNECTION: LESSONS FROM BANK MUAMALAT INDONESIA & BAITULMAAL MUAMALAT AFFILIATION - Bayinah, Ai Nur; Said, Muhammad; Suparta, Munzier (Bank Indonesia, 2021)
This research aims to explore the model of interconnection between the Islamic Bank and Zakat Management Organisation, as the two represent the implementation of Islamic economics in Indonesia. Using the Group Method of Data Handling (GMHD) tool to discern the strength of the relationship between the two representative entities, Bank Muamalat Indonesia and Baitulmaal Muamalat, it also followed the hyper postphenomenology approach to sharpen the result by obtaining essential confirmation from key informants with respect to determining the ideal model. The result showed a robust and reciprocal correlation between the account variables and its influence was statistically significant. Furthermore, it was interpreted as an effort to improve the image of the banking system while providing added value, forms of corporate responsibility and a spirit of service to customers. The results led to convergence on the formulation of the ideal model, which depends on the moral intentions of the owners of capital, government alignment and the literacy of directors, control needs and public awareness. Thus, it bridges the findings of previous studies and recommends a model that inseparable moral economic instruments. ACKNOWLEDGMENT This publication was made possible by the award from Bank Indonesia Institute. The author is grateful to the reviewers, Prof. Dr. Raditya Sukmana and Prof. Dr. Dian Masyita, for their guidance in refining this paper. Thanks to Mr. Donny Setiawan for improving the writing and to BMI, BMM, BAZNAS, Ministry of Religion Affairs RI, STEI SEBI, UIN Jakarta, and all colleagues, for supporting this research.